Microorganisms and Culture and Sensitivity Pattern in Chronic Suppurative Otitis Media in a Tertiary Care Hospital - Shrestha, Krishna Sundar; Madhup, Surendra Kumar; Shrestha, Bikash Lal; Pokharel, Monika; Dhakal, Ashish (Journal of College of Medical Sciences-Nepal, 2021)
Introduction CSOM is defined as persistent or intermittent infected discharge of more than three months duration through the perforated or non intact tympanic membrane caused by bacteria, fungi and virus resulting in inflammation of mucosal lining that often results in partial or total loss of tympanic membrane and ossicles. The aim of study was to study the current bacteriological profile responsible for the disease. Methods This descriptive cross sectional study was carried out at the department of Ear , Nose and Throat (ENT) and Head and Neck Surgery (HNS) in a tertiary care centre from January 2019 to December 2020. Ethical approval was taken from Institutional Review Committee (Reference number 52/2021). A convenient sampling method was used and data analysis was done in Microsoft Excel . Point estimate at 95% confidence interval was calculated along with frequency and proportion for binary data. Results There were a total of 324 patients included in the study. The age range was from five to sixty-eight years. Most patients were of the age group below 10 years. There were a total of 178 males and 146 females. The most common organism isolated were Staphylococcus aureus 145 (44.8%) and Psedomonas aeruginosa 86 (26.6%). Conclusions Staphylococcus aureus and Pseudomonas aeruginosa were the most common organisms responsible for chronic suppurative otitis media in our study. Keywords: chronic suppurative otitis media, Staphyllococcus aureus.